THE "TERRITORY OF CHILDHOOD": CONTENT, COMPONENTS, CONDITIONS OF DESIGNING - Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article based on the analysis of the needs of the participants of the educational process in the pre–school educational organization (PEO) determines the essence of the concept “the territory of childhood”, components and conditions of its designing. The materials contain the results of study of the problems and advantages of the educational space of a modern preschooler (using the example of Pskov city), which characterize the peculiarities of a child’s sociocultural development and the requirements for equipping the “the territory of childhood”.